Advocacy for human capital development through entrepreneurship education: Preparing undergraduates towards self-employment - Udodiugwu, Michael Ikenna; Eneremadu , Kingsley Enyinna; Njoku, Christian Onwuegbuchem; Obiakor, Ugochukwu Jude; Ilonze, Uju Gloria (Goodwood Publishing, 2025)
Purpose: The objective was to assess the impact of entrepreneurship education on human capital development. Research Methodology: This study employed a descriptive survey methodology, focusing specifically on students in their 300-level business education and business administration programs. The sample was drawn from selected Universities in Anambra and Imo states, Nigeria. To analyze data effectively, the study utilized a linear regression model, which allowed us to test the hypotheses we had formulated for this research rigorously. Results: This study uncovered compelling evidence that entrepreneurship education plays a crucial role in enhancing human capital development. Specifically, it fosters critical skills, innovative thinking, and practical knowledge. Limitations: This study was conducted with a specific focus on a sample of 440 undergraduate students, carefully selected from various universities located in two southeastern states of Nigeria. This deliberate choice of participants allows us to gain insights that reflect the unique educational context of the region. Contribution: This study has significantly enhanced our understanding of the challenges faced by undergraduates regarding white-collar job opportunities in the country. It has highlighted the reality that many of these positions may be increasingly out of reach due to various economic and competitive factors.